1990
DOI: 10.1111/j.1399-302x.1990.tb00645.x
|View full text |Cite
|
Sign up to set email alerts
|

The formation of hydrogen sulfide and methyl mercaptan by oral bacteria

Abstract: The capacity to form volatile sulfur compounds was tested in bacteria isolated from subgingival microbiotas and in a representative number of reference strains. A majority of the 75 tested oral bacterial species and 7 unnamed bacterial taxa formed significant amounts of hydrogen sulfide from L-cysteine. The most active bacteria were found in the genera Peptostreptococcus, Eubacterium, Selenomonas, Centipeda, Bacteroides and Fusobacterium. Methyl mercaptan from L-methionine was formed by some members of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
385
0
21

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 445 publications
(415 citation statements)
references
References 55 publications
9
385
0
21
Order By: Relevance
“…Awano et al (31) indicated a relationship between the presence of periodontopathic bacteria, such as Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia and Toreponema denticola, in saliva and oral malodor. In addition to periodontopathic bacteria, many oral bacteria can produce H2S and CH3SH in vitro (33). In the current study, PYC gum chewing for 4 wk resulted in a significant decrease for oral hydrogen sulfide-producing organisms (OHOs) in saliva compared with the baseline (Table 4), whereas no effect was observed in the placebo gum group.…”
Section: Discussionmentioning
confidence: 68%
“…Awano et al (31) indicated a relationship between the presence of periodontopathic bacteria, such as Porphyromonas gingivalis, Prevotella intermedia, Tannerella forsythia and Toreponema denticola, in saliva and oral malodor. In addition to periodontopathic bacteria, many oral bacteria can produce H2S and CH3SH in vitro (33). In the current study, PYC gum chewing for 4 wk resulted in a significant decrease for oral hydrogen sulfide-producing organisms (OHOs) in saliva compared with the baseline (Table 4), whereas no effect was observed in the placebo gum group.…”
Section: Discussionmentioning
confidence: 68%
“…Further, H2S in hibits myeloperoxidase and catalase (9). The high concentration of H2S in peri odontal pockets (21,24) may well orig inate from the degradation of cysteine by oral microbiota (25,26). We suggest that the number of sulfate-reducing bacteria in periodontal pockets and also their contribution to H2S produc tion are low due to the limited availabil ity of the energy source sulfate in the environment.…”
Section: Discussion Tmentioning
confidence: 98%
“…BANA testi Porphymonas gingivalis, Treponema denticola ve Tannerella forsythia gibi periodontal hastalıkla ilişkili ve USB'nin üretimini önemli ölçüde arttıran mikroorganizmaların varlığını gösterir. [41][42][43] İndol Testi, proteinlerin, peptidlerin ve amino asitlerin tükürükte gram negatif anaerobik bakterilerce bozulmasıyla ağız kokusuna sebep olan ürünler ortaya çıkar. Uçucu sülfür bileşenlerinden sistein ve indol, triptofandan ortaya çıkan iki ana koku bileşenidir.…”
Section: Mikrobiyal Ve Kimyasal Testlerunclassified